Conservative approach to a rare case of persistent sciatic artery with iatrogenic femoral arteriovenous fistula: a case report - Wang, Lizhao; Gu, Yan; Yang, Sen (Frontiers in Surgery, 2025)
Persistent sciatic artery (PSA) is a rare anatomic variant disease with an incidence of approximately 0.025%–0.05% it is considered to be an axial congenital vascular malformation, which may be related to the failure of sciatic artery degeneration and iliofemoral artery dysplasia. Some patients may be asymptomatic, while others experience chronic pain, thrombosis, and aneurysm formation. We report the case of a 63-year-old female patient with a superficial femoralartery (SFA)-common femoral vein (CFV) arteriovenous fistula found on ultrasound of the lower extremities due to soreness and numbness of the lower limbs. Interventional surgery and computed tomography were performed to close the internal fistulas and detect the PSA. A coated stent graft was inserted to close the arteriovenous fistula. After 1-mongth follow-up, lower limb discomfort disappeared, and she was administered symptomatic treatment with anticoagulation and swelling reduction medication. Six months after surgery, computed tomography indicated the disappearance of internal fistula and good PSA progression. Lower extremity symptoms were considered to be related to the femoral arteriovenous fistula; therefore, no intervention was performed for the PSA, we only provided health education, such as reducing sedentary and right lying to prevent vascular lesions.